2017
DOI: 10.1038/s41598-017-03811-9
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Migratory Phenotype in a Metastasized Breast Cancer Cell Line via Downregulation of S100A4 and GRM3

Abstract: To investigate phenotypic and genotypic alterations before and after bone metastasis, we conducted genome-wide mRNA profiling and DNA exon sequencing of two cell lines (TMD and BMD) derived from a mouse xenograft model. TMD cells were harvested from the mammary fat pad after transfecting MDA-MB-231 breast cancer cells, while BMD cells were isolated from the metastasized bone. Compared to BMD cells, TMD cells exhibited higher cellular motility. In contrast, BMD cells formed a spheroid with a smoother and more c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 37 publications
2
17
0
1
Order By: Relevance
“…These findings suggested that blocking S100A4 signaling reduces the formation of high proliferative active breast cancer hybrid cells also carrying metastatic properties. Supportive evidence is presented by recent work demonstrating reduced migration and metastases of breast cancer cells following down-modulation of S100A4 [ 50 ].
Fig.
…”
Section: Resultsmentioning
confidence: 63%
“…These findings suggested that blocking S100A4 signaling reduces the formation of high proliferative active breast cancer hybrid cells also carrying metastatic properties. Supportive evidence is presented by recent work demonstrating reduced migration and metastases of breast cancer cells following down-modulation of S100A4 [ 50 ].
Fig.
…”
Section: Resultsmentioning
confidence: 63%
“…The 4T1.2 cell line was isolated from metastasized bone, and represents a breast cancer model of efficient metastasis to bone ( 20 ). The responses to AZD7762 and PD407824 were examined in monolayer cell cultures, three-dimensional (3D) spheroids ( 21 ), and 3D bio-printed bone constructs ( 22 ). While PD407824 is able to inhibit tumor growth and osteoclastogenesis, its ability to promote osteoblast development is limited ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…TMD cells were isolated from tumors of injected MDA-MB-231 in a mouse, while BMD cells were isolated from bone metastasis after cardiac injection of TMD cells 9 . Our previous work showed that TMD cells exhibited more migratory characteristics in vitro than BMD cells 10 . Of note, primary human breast cancer cells are estrogen receptor-positive (ER+) 25 , while TMD and BMD cells are ER-negative.…”
Section: Discussionmentioning
confidence: 94%
“…TMD cells were isolated from the mammary tumor resulting from the injection of MDA-MB-231 cells to the mammary fat pad of NOD/SCHID mouse, while BMD cells were harvested from the metastasized bone 9 . Compared to BMD cells, it is reported that TMD cells exhibits higher cellular motility 10 .…”
Section: Introductionmentioning
confidence: 99%